Structure, health benefits and identification of chokeberry polyphenols: A comprehensive review - Ivana Buljeta; Lidija Jakobek; Daniela Kenjerić; Anita Pichler; Josip Šimunović; Mirela Kopjar (Croatian Journal of Food Science and Technology, 2024)
Polyphenols receive special attention from consumers and researchers due to their proven health benefits. They are present in different plants, and chokeberries are one of the significant polyphenol sources. Polyphenols found in chokeberries belong to the groups of phenolic acids, anthocyanins, proanthocyanidins, flavonols and flavanols. The highest concentration found in chokeberries belongs to proanthocyanidins followed by anthocyanins. The analysis of polyphenols is very demanding due to the great diversity and presence of conjugated forms. So, development of sensitive, rapid, and accurate analytical methods for analysis of polyphenols is very important. Liquid chromatography is a promising technique for polyphenols analysis, especially one equipped with mass spectrometry that gives additional information about molecular mass and structure. In this review, relevant studies conducted on the analysis of chokeberry polyphenols are presented.